Efficacy of Antibodies Conferred by the Recombinant Outer Membrane Protein H on Killing of Pasteurella multocida Strains by Complement-mediated Killing Assay - Tepsukalag, Panuwat; Korkerd, Udsanee; Muangthai, Korkiat; Uthi, Ratchanee; Rojanasthien, Suvichai; Sthitmatee, Nattawooti (Journal of Mahanakorn Veterinary Medicine, 2018)
Outer membrane protein H (OmpH) is one of the major outer membrane protein found in membrane protein of the Pasteurella multocida, a causative animal pathogen of bovine hemorrhagic septicemia. In this study, we have evaluated the efficacy of antibodies which was immunized by the recombinant outer membrane protein H (rOmpH) expressed in Escherichia coli expression vector system. Polyclonal antibody against rOmpH was prepared in rabbit and performed as a source of antibody in the complement mediated killing assay. The results showed that there was a significant increase in killing of P. multocida when anti-rOmpH rabbit serum was used as the source of antibody compared with using the infected P. multocida bovine serum or antibody-free P. multocida bovine serum as the source of antibody. These results suggested that the antibody induced by the rOmpH could induce the activation of complement to destroy pathogenic strains of P. multocida. The killing of P. multocida by anti-rOmpH antibody was significant higher than serum from infected with P. multocida and non-vaccinated group (P < 0.05). In conclusion, antibody raised against rOmpH can destroy P. multocida strains in a laboratory level.